2008
DOI: 10.1073/pnas.0806319105
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 regulates lifespan as distinct from disease onset in prion disease

Abstract: Prion diseases are fatal, transmissible, neurodegenerative diseases caused by the misfolding of the prion protein (PrP). At present, the molecular pathways underlying prion-mediated neurotoxicity are largely unknown. We hypothesized that the transcriptional regulator of the stress response, heat shock factor 1 (HSF1), would play an important role in prion disease. Uninoculated HSF1 knockout (KO) mice used in our study do not show signs of neurodegeneration as assessed by survival, motor performance, or histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 59 publications
(68 reference statements)
1
54
1
Order By: Relevance
“…While being a prominent longevity factor in nematodes (27,28), the influence of HSF1 on mammalian lifespan has been little explored. In some strains, Hsf1 compromise has no effect on lifespan (5,29). However, we found that in the mixed background used for our NPcis experiments, Hsf1 knockouts had a shorter lifespan than Hsf1 +/+ controls.…”
Section: Figurecontrasting
confidence: 38%
“…While being a prominent longevity factor in nematodes (27,28), the influence of HSF1 on mammalian lifespan has been little explored. In some strains, Hsf1 compromise has no effect on lifespan (5,29). However, we found that in the mixed background used for our NPcis experiments, Hsf1 knockouts had a shorter lifespan than Hsf1 +/+ controls.…”
Section: Figurecontrasting
confidence: 38%
“…We performed behavioral testing on PrP KOs and controls neural tissue during prion disease. We have recently implicated heat shock factor 1 as a mediator of protection against prion disease in vivo 12 and other research suggests that inflammation is a major contributor to prion pathogenesis. 13 Beyond these observations, the molecular mechanism(s) of prion-induced neuronal toxicity remain unresolved.…”
Section: Resultsmentioning
confidence: 99%
“…This response is regulated mainly at the level of transcription by heat shock transcription factor 1 (HSF1) (13)(14)(15). HSF1 protects cells from exposure to extreme temperatures, by inducing the expression of HSP (16)(17)(18)(19), and from various pathophysiological conditions, such as age-related neurodegenerative diseases (20)(21)(22)(23). Because HSF1 can sense even a mild increase in temperature, it has been suggested to play roles in the regulation of genes for inflammatory cytokines (24).…”
mentioning
confidence: 99%